Hell's march - Anderson, Taylor, 1963- (The Artillerymen series, 2022)
"Major Lewis Cayce will need to use every weapon in his arsenal to keep his stranded men alive on a deadly alternate Earth in this gripping new adventure set in the world of the New York Times bestselling Destroyermen series. It is 1848, and a full year after being shipwrecked on another, far stranger and more dangerous Earth on their way to fight Santa Anna in the Mexican-American War, Lewis Cayce and his small group of artillerymen, infantrymen, and dragoons have made friends in the Yucatán, helped build an army, and repulsed the first efforts of the blood-drenched Holy Dominion to wipe their new friends out. As an even more radical cult of Blood Priests arises and begins to pursue its own path to power, the Dominion can't let its defeat stand. It must crush the heretics and expel them from the land it has claimed. Fortunately, Lewis Cayce is a professional. He understands defense can only result in a stalemate at best, and a stalemate with the more populous Dominion will only lead to defeat in the end. The lucky few will be enslaved. The rest will be sacrificed in the most horrific way imaginable. The only hope his new allies have is to win-and to do that, his little army must attack the most powerful and diabolical enemy on the planet in its own territory. Achieving victory will take all Lewis's imagination, the courage and trust of his soldiers-and all the round shot and canister his tiny band of artillerymen can slam out"--